The Management of Social Studies Learning In Elementary Schools In Minahasa Regency - Boby A. Lompoliuw; Harol R. Lumapow; Ruth Umbase; Marien Pinontoan (International Journal of Education, Information Technology, and Others, 2026)
This study aims to describe the management of Social Studies learning in elementary schools in Minahasa Regency. The focus of the study includes learning planning, learning implementation, learning evaluation of Social Studies. This study employed a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observations, and documentation. The research informants consisted of school principals and elementary school teachers. Data analysis techniques included data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation.The results of the study indicate that: (1) Social Studies learning planning has been carried out through the preparation of learning instruments, but it remains largely administrative in nature; (2) The implementation of Social Studies learning is still predominantly conventional and teacher-centered; (3) The evaluation of Social Studies learning is mainly oriented toward written tests and has not fully implemented authentic assessment; (4) The supervision of Social Studies learning has been conducted through academic supervision, but it has not yet reached a comprehensive level and still tends to focus on administrative aspects; (5) The management of Social Studies learning is influenced by inhibiting factors, such as limited learning media and learning resources, as well as supporting factors, including teacher commitment and principal support.Based on the research findings, it is necessary to strengthen Social Studies learning management with a greater orientation toward improving the quality of the learning process through the development of innovative learning strategies, authentic assessment, and comprehensive academic supervision.